Breeding of medicinal and essential oil crops in VILAR: achievements and prospects - I. N. Korotkikh; D. N. Baleev; A. I. Morozov; P. G. Mizina; N. I. Sidelnikov (Вавиловский журнал генетики и селекции)
This review discusses the main methods of breeding material development, the current state, problems and prospects for medicinal and essential oil plants breeding. The relevance of this area has especially increased due to the sanctions, the resulting shortage of medicinal plants and their low quality, which does not meet the requirements of the pharmaceutical industry. To produce a stable plant raw material base, it is necessary to actively develop a breeding process to create new highly productive varieties of medicinal plants resistant to biotic and abiotic environments. In breeding with the use of modern molecular biological methods, related species and generic complexes of the All-Russian Research Institute of Medicinal and Aromatic Plants (VILAR) collection can be involved, where there is extensive original genetic material of medicinal, essential oil, rare and endangered species. In the breeding of medicinal and essential oil crops, traditional methods of individual and individual-family selection, polyploidy, chemical mutagenesis and a combination of methods to obtain original breeding material are still promising. VILAR has created more than 90 varieties of medicinal and essential oil crops, most of which have been approved for use throughout the Russian Federation.